Point-of-care ultrasound of peripheral nerves in the diagnosis of Hansen's disease neuropathy - Voltan, Glauber; Filho, Fred Bernards; Leite, Marcel Nani; De Paula, Natália Aparecida; Santana, Jaci Maria; Silva, Claudia Maria Lincoln; Barreto, Josafá Gonçalves; Da Silva, Moises Batista; Conde, Guilherme; Salgado, Claudio Guedes; Frade, Marco Andrey Cipriani (Frontiers in Medicine, 2022)
Introduction:Hansen’s disease (HD) is the most common cause of treatable peripheral neuropathy in the world that may or may not involve skin manifestations and physical examination based on simplified neurological evaluation is a subjective and inaccuracy procedure. High-resolution ultrasound (HRUS) can be used to evaluate peripheral nerves and is a validated technique of good reproducibility, permitting a detailed and precise exam. Objectives:we proposed to stablish the objective criteria of the measurements of the CSAs absolute values of the peripheral nerves and their indexes of the ∆CSA and ∆TpT in the diagnosis of Hansen’s disease neuropathy as compared to healthy voluntaries. Materials and methods:In municipalities from different regions of Brazil we selected at random 234 volunteer Brazilian patients diagnosed with leprosy to be submitted to peripheral nerve echography and compared to 49 of healthy Brazilian volunteers. Results:HD assessed by HRUS is a primarily neural disease that leads to multiple hypertrophic mononeuropathy characterized by CSA values exceeding normal limits (Med CT=10.2 mm2; UT=9.8 mm2; UPT=9.3 mm2; CFFH=18.3 mm2; T=9.6 mm2) and the pattern of asymmetry (∆CSA>2.5mm2 with RR 13) and focality (∆TPT>2.5 mm2 with RR 6.4) of this thickening has higher sensitivity (76,1%) and specificity (87,8 %) for its early diagnosis that laboratory tests. Analyzing each subject, the percentage of thickened nerves detected among the total number of nerves assessed was higher among HD patients than among healthy individuals (p<0.0001). Individuals with two or more thickened nerves having a 24.1 times higher relative risk (95%CI: 6.74 to 88.98) to have HD.